2010
DOI: 10.1016/j.ejcts.2009.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of untreated mild-to-moderate mitral regurgitation at the time of isolated aortic valve replacement on late adverse outcomes☆

Abstract: Despite the significant reduction after isolated AVR, preoperative mild-to-moderate MR is an independent risk factor impacting long-term functional outcome. Our results suggested that the concomitant mitral valve surgery for mild-to-moderate MR is warranted, especially in patients with reduced left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
5
32
1
1
Order By: Relevance
“…Moreover, gradual restoration of pump function has been observed clinically in asymptomatic patients with mild to moderate MR and LV systolic dysfunction before intervention (32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gradual restoration of pump function has been observed clinically in asymptomatic patients with mild to moderate MR and LV systolic dysfunction before intervention (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is substantial disagreement in the literature over the proportion of patients that will experience improvement in MR after AVR and the degree of improvement that can be expected is not well defined. 1 For these reasons, the appropriate management of intermediate degrees of MR in the setting of AVR is undefined and remains controversial, with some authors advocating for a more aggressive surgical approach 2,3,5,8 and others advocating a more conservative approach. 9,10 No randomized controlled clinical trials that address this issue have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by ruel et al 6 significant MR was associated with a higher incidence of heart failure symptoms in patients which had undergone aVr for as, but only when it was associated with at least one risk factor (left atrial diameter >5 cm, peak aortic gradient >60 mm hg, mean aortic gradient >40 mm Hg and atrial fibrillation). Takeda et al 9 showed a significantly higher rate of re-hospitalization for heart failure in patients with concomitant significant MR compared with non/trivial and, among patients with significant Mr, a trend for a higher re-admission rate for patients without any improvement in Mr after aVr. on the other hand, the partNer study 7 showed an improvement in Nyha functional class after both surgical aVr and taVr which was independent on the presence and severity of concomitant Mr. a similar result emerged from a study by toggweiler et al 12 on patients undergoing taVr, with a general improvement in Nyha class regardless of Mr grade.…”
Section: Significant Mr and Functional Status In Patients Undergoing Avrmentioning
confidence: 99%
“…several studies compared mortality in patients undergoing surgical AVR with and without significant MR (considered at least moderate or ++/++++): most of them showed an excess in mortality in patients with significant MR compared to those with no/trivial/mild Mr (4-7), but some failed to demonstrate this association 8,9 . a 2011 meta-analysis performed on 17 studies concluded that patients with moderate/severe Mr had higher mortality compared to mild or no Mr at 30 days (or 0.41; CI at 95%: 0.24-0.72), and worse survival at 3 years (hr 0.49; CI at 95%: 0.35-0.69), 5 years (hr 0.46; CI at 95%: 0.34-0.61) and 10 years (hr 0.61; CI at 95%: 0.40-0.92)after aVr 10 .…”
Section: Impact Of Significant Mr On Mortality In Patients Undergoingmentioning
confidence: 99%